In Silico Design and Validation of CRISPR-Cas13a System as a Potential Antiviral for SARS-CoV-2 in Indonesia - Alfero Putra Iryanto; Christy; Muhammad Farrel Ewaldo; Anggia Prasetyoputri; Ratih Asmana Ningrum; Riza Arief Putranto; Akhirta Atikana (Nusantara Science and Technology Proceedings)
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a worldwide pandemic of coronavirus disease (COVID-19). Indonesia is one of the countries with large numbers of positive cases in Asia with certain dominant variants. Currently, there are no specific therapeutic agents against SARS-CoV-2. Therefore, the development of specific and effective therapeutic tools is urgently needed to overcome the pandemic. This study designed a CRISPR-Cas13a system strategy as a potential anti-SARS-CoV-2. We utilized comprehensive bioinformatics methods to identify a unique segment in the SARS-CoV-2 consensus sequence from Indonesia that is different from the related segment in the SARS-CoV. This unique segment was used as a specific target for SARS-CoV-2 Spike Protein to design a set of crRNA libraries. Off-target analysis and molecular docking simulation were performed to validate the specificity and to analyze interactions among the crRNA candidates, target RNA, and Cas13a. Our study identified a 17 amino acid unique segment on the Receptor Binding Domain (RBD) region. By using that unique segment, a total of 12 crRNA candidates were selected based on their GC content. Finally, based on the off-target and molecular docking validation, four crRNAs were selected as potential candidates for CRISPR-Cas13a-based antivirals. Although further validation with in vitro assays is important, the present study provides a comprehensive demonstration regarding the potential of CRISPR-Cas13a as a strategy for SARS-CoV-2 antiviral development. Considering the specific property of the CRISPR system, the present methodology can also be utilized to develop novel antiviral candidates for other RNA viruses.